Muftiyyatul Ummah The Implementation of a School Information Management System and Its Impact on Report Card Management at SD Intan Al-Sali: The Implementation of Management Information Systems on the Effectiveness of Report Card Management in Primary Schools - Ummah, Muftiyyatul; Hariyanto, Teguh (Epistemic: Jurnal Ilmiah Pendidikan, 2025)
The integration of digital technology in elementary school academic administration still faces various challenges, especially in the management of student report cards. This study aims to examine the effectiveness of the implementation of the e-report card system at SD Intan Al-Sali Bandung City as part of the School Management Information System. The study used a descriptive qualitative approach with data collection techniques through interviews, observation, and document analysis. Participants consisted of 10 teachers, 3 administrative staff, and school management during the two-month implementation. The results showed that the e-report card increased the speed and accuracy of grade input, facilitated access to information for parents, and improved administrative efficiency. However, obstacles such as the limited internet network and the absence of the autosave feature are still obstacles. The study concludes that the successful implementation of e-report cards is highly dependent on infrastructure support and continuous user training. These findings can be a reference for schools and policy makers in encouraging the digitalization of ICT-based academic administration.